Optimizing HPV vaccine effectiveness: impact of vaccination age and dose schedule on immunogenicity and cervical cancer prevention - Rostami Varnousfaderani, Mehran; Khoshnazar, Zahedeh; Zeratie, Hamidreza; Hosseini Koukamari, Parisa (Frontiers in Public Health, 2025)
Cervical cancer is the fourth most common cancer among women globally, claiming over 443,000 lives annually, with 98% of these deaths occurring in developing countries. Vaccination against human papillomavirus (HPV) is a preventive strategy. This review investigates the role of age at vaccination and the number of doses in determining vaccine effectiveness. Articles from 2013 to 2023 were retrieved from PubMed, Scopus, SID, and Google Scholar using keywords related to HPV, vaccine, age, and dose. The findings suggest that the highest vaccine effectiveness is observed in younger age groups (ages 9–14: 74–93%) and decreases with age. Studies indicate that while three doses provide optimal protection, a single dose may also confer significant benefits in younger populations. These findings underscore the importance of timely vaccination and adherence to dosing schedules for maximizing vaccine impact.